Local Motors, Inc., and Industry City Distillery - Hisrich, Robert D.; Kearney, Claudine ([London] : SAGE, 2016)
Using Local Motors, a company that manufactures co-created vehicles and components, and Industry City Distillery, a vodka producer, this case looks at the innovation possible with customized small-scale manufacture and design.
Originally Published in: Hisrich, R. D., & Kearney, C. (2013). Scenario: Local Motors, Inc., and Industry City Distillery. In Managing innovation and entrepreneurship (pp. 172-174). Los Angeles: SAGE Publications, Inc. ISBN: 9781452241357.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Small business -- Management -- Case studies; Creative ability in business -- Case studies